Safety and effectiveness of seahorse extract (Hippocampus comes L.) on the hematological profile and body weight of male rats induced by depo medroxyprogesterone acetate. - Mundijo, Trisnawati; Suyatna, Franciscus Dhyanagiri; Wibowo, Agung Eru; Yusra, Yusra; Midoen, Yurnadi Hanafi (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The objective of this study was to investigate the effectiveness and safety of seahorse (Hippocampus comes L.) extract on hematological profile and body weight on rats induced by depo medroxyprogesterone acetate (DMPA). Materials and Methods: Thirty adult male Sprague-Dawley rats with 200–250 gm and 8 weeks old. All rats were intramuscularly administered 1.25 mg/kg BW DMPA Merck Depo Geston at 150 mg/3 ml. The animals were divided into five main groups (6 each), consisting of aquadest (G1), CMC 1% (G2), seahorse extract (SE) dose 150 mg/kg BW (G3), 225 mg/kg BW (G4), and 300 mg/ kg BW (G5). All rats were weighed until the end of the treatment week. Results: The hematological profile and body weight of the group given SE tended to increase compared to the group not given extract; however, our hematological profile and body weight were in the normal range for rats. Conclusion: We find that SE enhances the effectiveness of the hematological profile, body weight, and safety of rats induced by DMPA. J. Adv. Vet. Anim. Res., 11(3): 717-721, September 2024 http://doi.org/10.5455/javar.2024.k822